Biological Sex and Sex Hormone Impacts on Deficits in Episodic-Like Memory in a Rat Model of Early, Pre-motor Stages of Parkinson's Disease - Conner, Meagan R.; Jang, Doyeon; Anderson, Brenda J.; Kritzer, Mary F. (Frontiers in Neurology, 2020)
Episodic memory deficits are among the earliest appearing and most commonly occurring examples of cognitive impairment in Parkinson's disease (PD). These enduring features can also predict a clinical course of rapid motor decline, significant cognitive deterioration and the development of PD-related dementia. The lack of effective means to treat these deficits underscores the need to better understand their neurobiological bases. The prominent sex differences that characterize episodic memory in health, aging and in schizophrenia and Alzheimer’s disease suggest that neuroendocrine factors may also influence episodic memory dysfunction in PD. However, while sex differences have been well documented for many facets of PD, sex differences in, and sex hormone influences on associated episodic memory impairments have been less extensively studied and have never been examined in preclinical PD models. Accordingly, we paired bilateral neostriatal 6-hydroxydopamine (6-OHDA) lesions with behavioral testing using the What-Where-When Episodic-Like Memory (ELM) Task in adult rats to first determine whether episodic-like memory is impaired in this model. We further compared outcomes in gonadally intact female and male subjects, and in male rats that had undergone gonadectomy – with and without hormone replacement, to determine whether biological sex and/or sex hormones influenced the expression of dopamine lesioned-induced memory deficits. These studies showed that 6-OHDA lesions profoundly impaired recall for all memory domains in male and female rats. They also showed that in males, circulating gonadal hormones powerfully modulated the negative impacts of 6-OHDA lesions on What, Where and When discriminations in domain-specific ways. Specifically, the absence of androgens was shown to fully attenuate 6-OHDA lesion-induced deficits in ELM for 'Where' and to partially protect against lesion-induced deficits in ELM for 'What'. In sum, these findings show that 6-OHDA lesions in rats recapitulate the vulnerability of episodic memory seen in early PD. Together with similar evidence recently obtained for spatial working memory, the present findings also showed that diminished androgen levels provide powerful, highly selective protections against the harmful effects that 6-OHDA lesions have on memory functions in male rats.